Interest rates, money, and banks in an estimated euro area model - Kai Christoffel; Andreas Schabert (European Central Bank (ECB), 2015)
This paper examines monetary transmission and macroeconomic shocks in a medium scale macroeconomic model with costly banking estimated for euro area data. In addition to data on measures of real activity and prices, we include data on bank loans, loan rates, and reserves for the estimation of the model with Bayesian techniques. We find that loans and holdings of reserves affect banking costs to a small but significant extent. Furthermore, shocks to reserve holdings are found to contribute more to variations in the policy rate, inflation and output than shocks to the feedback rule for the policy rate. Hence, holdings of central bank money, which is typically neglected in the literature, plays a substantial role for macroeconomics dynamics. The analysis further shows that exogenous shifts in banking costs hardly play a role for fluctuations in real activity and prices, even during the recent financial crisis.
Keywords: C54; E52; E32; 330; Bayesian estimation; central bank money supply; costly banking; financial shocks